(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: This research focuses on minimizing the Roundness Error (RE) of LDX 2205 duplex stainless steel by comparing the performance of the TiCN drill bit and uncoated HSS drill bit in the novel CNC drilling process. Materials and Methods: The materials used for drill bits are Titanium Carbonitride (TiCN) coated HSS drill and uncoated HSS drill bit. LDX 2205 duplex stainless steel was used as workpiece. A total of 40 specimens were divided into 2 groups with 80% G-Power calculator, to measure the RE of the workpiece machined with the two drill bits in the novel CNC drilling machine. The control factors were spindle speed, cutting force, tool geometry, rate of feed, and drill depth. Results: Observed results were recorded and analyzed using SPSS Software. Final experimental values of RE were investigated and obtained, having mean RE value of 0.0400 mm for the HSS drill bit and mean RE value of 0.0287 mm for the TiCN drill bit. Significance value of this study was 0.032 which is less than 0.05 (p<0.05). Conclusion: Within the limits of this study, TiCN drill bit had lower RE when compared to the HSS drill bit in the novel CNC drilling of LDX 2205 duplex stainless steel.